Cost-benefit analysis of on-farm grain storage hermetic bags among small-scale maize growers in northwestern Ethiopia. (May 2021) - Alemu, Gashaw Tenna; Nigussie, Zerihun; Haregeweyn, Nigussie; Berhanie, Zewdu; Wondimagegnehu, Beneberu Assefa; Ayalew, Zemen; Molla, Dessalegn; Okoyo, Eric Ndemo; Baributsa, Dieudonne
Abstract: Farmers continue losing substantial quantities of grain during storage due to damages from pests including insects. Hermetic bags, being promoted in Ethiopia, could be viable alternatives to traditional methods and insecticides that are commonly used by farmers to store grain. However, the economics and determinants behind farmers' decisions to use different storage methods are poorly understood. This study sought to ascertain the economics of hermetic grain storage technology among 450 representative small-scale maize farmers in northwestern Ethiopia. Gross margin (GM), and the marginal rate of return (MRR) were employed to estimate the economic costs and benefits of storage methods, while a multivariate probit regression model was employed to analyze the determinants of farmers' decision to store maize with a given storage method. The results show that farmers used a combination of different storage techniques: 19.6% did not store grain, 87.8% used traditional methods with pesticide, and 66.7% used Purdue Improved Crop Storage (PICS) hermetic bags. Farmers who used hermetic bags also used other mentioned storage techniques. PICS had the highest GM (US$21.77 100 kg −1 ) and MRR (3.196), indicating that they were the most profitable. Moreover, a household could obtain an additional net cash flow of US$5.02 100 kg −1 PICS bag per season after 9.6 months of storage. Farmers' decisions to use PICS bags were influenced by several factors including access to information, the initial cost, and storage capacity of the technology. Thus, increasing awareness and improving supply chain efficiency to reduce the cost of the PICS bags would improve adoption rates. Highlights: The PICS bag has been widely promoted to reduce storage loss in Ethiopia, but its economic viability are poorly studied. The cost and benefit of using PICS bags for maize storage in northwestern Ethiopia were analyzed in this study. PICS bags had the highest gross margin (US$21.77 100 kg −1 ) among storage options. Households' decision to adopt PICS bags were influenced by the initial cost of the technology, storage capacity, and access to information. Increasing awareness and improving the supply chain efficiency to reduce cost would improve adoption rates.